Concise account of recent S(N)2 ` grignard coupling reactions in organic synthesis - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
Over the past few decades studies oil controlling the chemo-, regio- and stereoselectivities of allylic Substitution reactions have been well documented in the literature and the S(N)2' Grignard coupling reaction has emerged as a very powerful tool ill selective carbon-carbon bond formation. This review focuses on all the recent synthetic developments in this special class of reactions. 1 Introduction 2 S(N)2' Grignard Coupling Reactions with Allylic Substrates 2.1 Allyl Halides 2.2 Allyl Acetates 2.3 Allyl Carbonates 2.4 Allyl Carbamates 2.5 Allyl Ethers 2.6 Allyl Silyl Ethers 2.7 Allyl Epoxides 2.8 Allyl Aziridines 2.9 Allyl Oxazolidinones 2.10 Allyl Thioethers 2.11 Allyl Benzotriazoles 2.12 Oxabicyclic Alkenes 2.13 Azabicyclic Alkenes 2.14 Oxa-azabicyclic Alkenes 3 S(N)2' Grignard Coupling Reactions with Propargyl Substrates 3.1 Propargyl Acetates 3.2 Propargyl Silyl Ethers 3.3 Propargyl Epoxides 3.4 Propargyl Aziridines 3.5 Propargyl Dithioacetals 3.6 Propargyl Thioethers 4 S(N)2' Grignard Coupling Reactions with Bromoallenes 5 S(N)2' Grignard Coupling Reactions in Natural/Unnatural Product Synthesis 6 Conclusions.
Keywords: allylic substrates; bromoallenes; chiral/achiral S(N)2 ` Grignard coupling reactions; Natural products; propargyl Substrates

Facile synthesis of rubrolide E - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
A simple and efficient synthesis of rubrolide E (1e) has been demonstrated via Meerwein coupling reaction of para-anisyl-diazonium chloride with N-phenylmaleimide (2), regioselective reduction of para-anisylmaleic anhydride (4), Knoevenagel condensation of butyrolactone 5 with para-anisaldehyde and demethylation pathway.
Keywords: Knoevenagel condensation; Meerwein coupling; N-phenylmaleimide; regioselective reduction; rubrolide E; Total synthesis

Simple synthesis of (+/-)-sarkomycin - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
A facile 6-step route to (+/-)-sarkomycin in 17% overall yield has been described via Michael addition of nitromethane to 2-hydroxymethyl-2-cyclopentenone, oxone-induced oxidative Nef reaction, and acid catalyzed dehydration.
Keywords: (+/-)-sarkomycin synthesis; 2-hydroxymethyl-2-cyclopentenone; Michael addition; nitromethane.; oxidative Nef reaction; Oxone

Synthesis of naturally occurring bioactive butyrolactones: maculalactones A-C and nostoclide I - Kar, Anirban; Gogoi, Sanjib; N. P. Argade (Tetrahedron, 2005)
Starting from citraconic anhydride (13), a simple multistep (9-10 steps) synthesis of naturally occurring butyrolactones maculalactone A (3), maculalactone B (1), maculalactone C (2) and nostoclide 1 (4) have been described with good overall yields via dibenzylmaleic anhydride (20) and benzylisopropylmaleic anhydride (27). The two anhydrides 20 and 27 were prepared by S(N)2' coupling reactions of appropriate Grignard reagents with dimethyl bromomethylfumarate (14), LiOH-induced hydrolysis of esters to acids, bromination of carbon-carbon double bond, in situ dehydration followed by dehydrobromination and chemoselective allylic substitution of bromoatom in disubstituted anhydrides 19 and 26 with appropriate Grignard reagents. The NaBH4 reduction of these anhydrides 20 and 27 furnished the desired lactones 21 and 29, respectively. The lactone 21 on Knoevenagel condensation with benzaldehyde, furnished maculalactone B (1), which on isomerization gave maculalactone C (2). Selective catalytic hydrogenation of 1 gave maculalactone A (3). The conversion of lactone 29 to nostoclide 1 (4) is known. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: dimethyl bromomethylfumarate; disubstituted maleic anhydrides; maculalactone A-C; NaBH4 reductions; nostoclide 1; S(N)2 ` Grignard couplings; synthesis

Chemistry of recently isolated naturally occurring quinazolinone alkaloids - Mhaske, Santosh B.; N. P. Argade (Tetrahedron, 2006)
The present review portrays a concise account of the isolation, bioactivity, and synthesis of bioactive quinazolinone-based natural products for the period 1983-2005 and the recent developments in the area of complex quinazolinone natural products with a special emphasis on new synthetic routes and strategies. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1983-2005; bioactivity; concise account; isolation; natural quinazolinones; synthesis

Efficient amano PS-catalyzed chemo-, regio- and enantioselective hydrolysis of (+/-)-2,3-di-O-acetyl-2-C-methyl-D-erythrono-1,4-lactone: a facile preparation of bioactive natural products (-)-saccharinic acid lactone and potassium (2R,3R)-2,3,4-trihydr - Gogoi, Sanjib; N. P. Argade (Tetrahedron-Asymmetry, 2006)

Facile synthesis of 1,3,7-trihydroxyxanthone and its regioselective coupling reactions with prenal: simple and efficient access to osajaxanthone and nigrolineaxanthone F - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2006)
A facile five-step synthesis of naturally occurring 1,3,7-trihydroxyxanthone has been described starting from 1,3,5-trimethoxybenzene via NBS-induced nuclear bromination, lithiation followed by an in situ benzoylation with methyl 2,5-dibenzyloxybenzoate, selective deprotection of the two benzyl groups, base-catalyzed intramolecular cyclization, and demethylations pathway with 62% overall yield. The regioselective coupling reactions of 1,3,7-trihydroxyxanthone with prenal in the presence of calcium hydroxide at room temperature and under thermal conditions at 140-150 degrees C have been demonstrated to exclusively obtain the natural products osajaxanthone in 75% yield and nigrolineaxanthone F in 98% yield, respectively.

Facile two-step chemoenzymatic access to natural germination inhibitor (+)-erigeronic acid A - Gogoi, Sanjib; N. P. Argade (Tetrahedron, 2006)
A facile two-step synthesis of natural germination inhibitor 5-butyl-3-oxo-2,3-dihydrofuran-2-yl-acetic acid [(+)-erigeronic acid A, 1] has been described via highly regioselective ring opening of (R)-acetoxysuccinic anhydride with the primary enolate of butyl methyl ketone, followed by an enzymatic hydrolysis and ail in situ dehydrative cyclization pathway with 77% overall yield. Oil the basis of the present chemoenzymatic approach, (R)-configuration has been assigned to the C-2 chiral centre of the natural erigeronic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: (+)-erigeronic acid; (R)acetoxysuccinic anhydride; natural germination inhibitor; primary enolate of butyl methyl ketone; synthesis

Haval-Argade contrathermodynamic rearrangement of alkylidenesuccinimides to alkylmaleimides via the corresponding isoimides: a general approach to alkyl and dialkyl substituted maleimides - Haval, Kishan P.; N. P. Argade (Tetrahedron, 2006)
A simple and efficient access to alkyl and dialkyl substituted maleimides has been demonstrated via the new contrathermodynamic rearrangement of (E)-alkylidenesuccinimides to alkylinaleimides. The (E)-alkylidenesuccinimides obtained from the Wittig-condensation of N-arylmaleimide with aliphatic aldehydes oil regioselective hydrolysis furnished the corresponding (E)-alkylidenesuccinanilic acids in 95-98% yields. The beta-alkylidenesuccinanilic acids oil treatment with cyanuric chloride in the presence of triethylamine gave the corresponding beta-alkylisomaleimides in 78-80% yields via the beta-alkylideneisosuccinimides with the exocyclic to endocyclic carbon-carbon double bond migration. The kinetically controlled products alkylisomaleimides in refluxing acetic acid furnished the thermodynamically controlled alkylinaleimides in 98% yield. The Wittig condensation of alkyl substituted isomaleimides/maleimides with aliphatic aldehydes gave the desired dialkyl substituted maleimides in high yields. A conversion of alpha-methylenesuccinanilic acids to alpha-methylisomaleimides has also been described, with 90% yield. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alkyl and dialkylmaleimides; contrathermodynamic rearrangement; isomaleimides; maleimides; wittig coupling

Facile chemo-, regio-, and diastereoselective approach to cis-3,5-disubstituted gamma-butyrolactones and fused gamma-butyrolactones - Baag, Md. Merajuddin; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
Chemoselective S(N)2' condensation of primary enolates of alkyl methyl ketones 2a-e with dimethyl bromomethylfumarate ( 1) followed by highly diastereoselective NaBH4 reduction of the ketone function in the formed ketodiesters 3a-e and the regioselective in situ lactonization of the unisolable intermediates 4a-e exclusively furnished the cis-3,5-disubstituted gamma-butyrolactones (+/-)-5a-e in very good yields. Similarly, the face-selective coupling reaction of cyclohexanone enolate with 1 to form a mixture of diastereomers in an 8: 2 ratio followed by a highly selective reductive cyclization of 9 plus 10 exclusively provided the cis-octahydrobenzofuran (+/-)- 12 in 70% overall yield.

Facile phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2+2] annulation reactions: an easy access to complex bioactive natural and unnatural benzopyran congeners - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
The complex bioactive natural and unnatural benzopyran congeners have been synthesized using one-/two-step approaches in very good yields from the reactions of two different dihydroxyphthalides, natural resorcyclic acid derivative, and trihydroxybenzophenone with citral and/or farnesal, via the phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions and three different thermal intramolecular cyclization reactions. The effects of the nature and the position of phenolic groups in the starting materials on the course of these cycloaddition reactions have also been described. Depending upon the absence or presence of intramolecular hydrogen bonding of the phenolic group with the carbonyl moiety in the starting materials, these phenol-driven intramolecular thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions either furnished the kinetically controlled products or directly formed the thermodynamically controlled rearranged products, respectively.

Facile S(N)2 ' coupling reactions of wittig reagents with dimethyl bromomethylfumarate: synthesis of enes, dienes, and related natural products - Patel, Ramesh M.; N. P. Argade (Journal of Organic Chemistry, 2007)

Hexamethyldisilazane-iodine induced intramolecular dehydrative cyclization of diamides: a general access to natural and unnatural quinazolinones - Kshirsagar, Umesh A.; Mhaske, Santosh B.; N. P. Argade (Tetrahedron Letters, 2007)
A simple and efficient general approach to various quinazolinone scaffolds, including peptidomimetic examples, has been demonstrated by employing HMDS/I-2 for the intramolecular dehydrative cyclization of diamides. The protecting groups -Boc, -Fmoc and -Cbz tolerated the present reaction conditions and we did not observe any racemization. The present protocol has also been used as a key step for the efficient four-step syntheses of the naturally occurring quinazolinones, sclerotigenin, (-)-circumdatin-F and (-)-fumiquinazoline-F. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: diamides; HMDS/I-2; intramolecular dehydrative cyclizations; natural and unnatural quinazolinones; synthesis

Reactions of o-aminothiophenol and o-aminophenyl disulfide with itaconic anhydride and (-)-dimenthyl itaconate: access to enantiomerically pure 1,5-benzothiazepines and benzothiazolyl-2-methylacrylic acid - Baag, Md. Merajuddin; Sahoo, Manoj Kumar; Puranik, Vedavati G.; N. P. Argade (Synthesis-Stuttgart, 2007)
{A facile chemo- and regioselective reactions of o-aminothiophenol (o-ATP) with itaconic anhydride is described. 1,5-Benzothiazepinyl-3-acetic acid is obtained in 81% yield via the exclusive Michael type addition of the thiol unit from o-ATP to the carbon-carbon double bond in itaconic anhydride followed by an intramolecular anhydride ring opening with an amine unit. The moderately stereoselective Michael type addition of the thiol unit from o-ATP to (-)-dimenthyl itaconate to obtain a mixture of diastereomers in a 7:3 ratio in 82% yield has been demonstrated. The reductive sulfur-sulfur bond cleavage in the dicarboxylic acid, 2({2-[2-(3-carboxybut-3-enoylamino)phenyidisulfanyl]phenylcarbamoyl\
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Synthesis of natural fimbrolides - Haval, Kishan P.; N. P. Argade (Synthesis-Stuttgart, 2007)

Facile air-oxidation of N-homopiperonyl-5,6-dimethoxyhomophthalimide: simple and efficient access to nuevamine - Wakchaure, Prasad B.; Easwar, Srinivasan; Puranik, Vedavati G.; N. P. Argade (Tetrahedron, 2008)
A facile six-step synthesis of naturally occurring (+/-)-nuevamine with 55% overall yield has been described, starting from methyl 2-(6-formyl-2,3-dimethoxyphenyl)acetate via the quantitative benzylic air-oxidation of the corresponding N-homopiperonyl-5,6-dimethoxy-homophthalimide to N-homopiperonyl-5,6-dimethoxyisoquinoline-1,3,4-trione as the key reaction, followed by base catalyzed regioselective alcoholysis of the trione with ring contraction, acid catalyzed dehydrative ring closure of the formed lactamol and decarboxylation pathway. (C) 2007 Elsevier Ltd. All rights reserved.

Facile biogenetic synthesis of pulcheotine A - Wakchaure, Prasad B.; N. P. Argade (Synthesis-Stuttgart, 2008)
Starting from homopiperonylamine and 4-methoxyphenylacetic acid, a facile biogenetic route to naturally occurring pulcheotine A has been demonstrated via Pictet-Spengler cyclization and two different air oxidation processes.
Keywords: 4-methoxyphenylacetic acid; homopiperonylamine; Pictet-Spengler cyclization; pulcheotine A; regioselective air oxidations

General strategy for the synthesis of natural and unnatural dialkylmaleic anhydrides - Haval, Kishan P.; N. P. Argade (Journal of Organic Chemistry, 2008)
Starting from alkylidenesuccinimides, a wide range of dialkylmaleic anhydrides have been synthesized via the generation of a carbanion on a succinimide unit and its condensation with various alkyl halides as the key reaction.

Synthesis of gymnoascolide A - Baag, Md. Merajuddin; N. P. Argade (Synthesis-Stuttgart, 2008)
Recently isolated 4-benzyl-3-phenylfuran-2,5-dione and antifungal gymnoascolide A have been synthesized using the chemoselective S(N)2' coupling of phenylmagnesium bromide with dimethyl 2-(bromomethyl)fumarate, chemoselective allylic substitution of bromide in 3-(bromomethyl)-4-phenylfuran-2,5-dione with phenylmagnesium bromide and regioselective N-Selectride-induced reduction of 3-benzyl-4-phenylfuran-2,5-dione as the key reactions.
Keywords: dimethyl (bromomethyl)fumarate; functionalized maleic anhydrides; gymnoascolide A; regioselective reduction; S(N)2 ` Grignard coupling reaction

Synthesis of norpandamarilactonines, pandamarilactonines, and pandanamine - Gogoi, Sanjib; N. P. Argade (Synthesis-Stuttgart, 2008)
A facile route to naturally occurring (+/-)-norpandamarilactonines A and B, (+/-)-pandamarilactonines A-D, and pandanamine has been described from 3-methylfuran-2(5H)-one, with a reductive intramolecular aza-Michael-type addition as the key step.
Keywords: 3-methylfuran-2(5H)-one; condensation; intramolecular aza-Michael reaction; pandamarilactonines

Facile approach to diverse range of 1,3-diaza-heterocycles: angular/linear selectivity paradigm and a remarkable intramolecular methyl migration - Kshirsagar, Umesh A.; N. P. Argade (Tetrahedron, 2009)
Starting from cyclic anhydrides and tert-butyl 2-aminobenzylcarbamate, simple and efficient synthesis of diverse range of kinetically controlled angular and thermodynamically controlled linear tricyclic and tetracyclic 1,3-diaza-heterocycles have been described via the intramolecular cyclizations of the corresponding imides/anilic acid esters. The effect of imide stability on the angular/linear product selectivity has also been described. The kinetically controlled angular products were successfully transformed to the corresponding thermodynamically controlled linear products by refluxing in methanol or methanol and acetic acid mixture. An interesting in situ 1,2-intramolecular methyl group migration has also been described. (C) 2009 Elsevier Ltd. All rights reserved.

Stereoselective synthesis of (+)-isoindolo-beta-carboline - Wakchaure, Prasad B.; Puranik, Vedavati G.; N. P. Argade (Tetrahedron-Asymmetry, 2009)
Starting from homophthalic anhydride and (S)-tryptophan, the stereoselective synthesis of (+)-isoindolo-beta-carboline has been described via the corresponding homophthalimide, its chemoselective oxidative ring contraction, and the intramolecular dehydrative ring closure followed by a geometry-specific demethoxycarbonylation. (C) 2009 Elsevier Ltd. All rights reserved.

Synthesis of the reported protoberberine gusanlung D - Wakchaure, Prasad B.; Easwar, Srinivasan; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from homopiperonylamine or phenethylamine with homophthalic anhydride or 3,4-methylenedioxyhomophthalic acid, respectively, facile syntheses of the reported structures of (+/-)-gusanlung D and (+/-)-isogusanlung d were accomplished via regioselective reductive dehydration of the corresponding homophthalimides followed by an intramolecular acid-catalyzed or radical cyclization pathway. Starting from the corresponding suitably ortho-halogenated homophthalimides, the syntheses of dehydrogusanlung and dehydroisogusanhing D were completed via regioselective reductive dehydration followed by an intramolecular Heck coupling reaction as the key steps. The analytical and spectral data obtained for all four synthetic compounds differed from the reported data for natural gusanling D, and therefore the structural assignment of the natural product needs to be revised.
Keywords: gusanlung D; Heck reaction; homophthalic anhydride; homopiperonyl amine; reductive dehydration

Total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from citraconic anhydride, the first total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol has been demonstrated via a stepwise route involving generation of an apiitol derivative followed by benzoylation.
Keywords: (+/-)-1; 3; 4; 5-tetragalloylapiitol; allylic hydroxylation; Natural products; osmium tetroxide

Bromine-induced facile synthesis of butenolides and spirobutenolides from sterically congested tetrasubstituted dialkyl alkylidene succinates - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2010)
Starting from sterically congested tetrasubstituted dialkyl alkylidene succinates, facile general approach to several dialkyl substituted butenolides and spirobutenolides with the generation of quaternary carbon center has been demonstrated via bromine-induced dealkylative regioselective intramolecular cyclization and dehydrobromination pathway. The mechanistic aspects involved in the formation of butenolides have been also described in brief.
Keywords: alkylidene succinates; bromine; butenolides; intramolecular cyclizations; spirobutenolides

Chemoselective coupling reactions of 5,7-dimethoxyphthalide with the remotely functionalized alkyl iodides: facile racemic synthesis of helicobacter pylori antibiotics - Singh, Mandeep; N. P. Argade (Journal of Organic Chemistry, 2010)
Highly chemoselective coupling reactions of 5,7-dimethoxyphthalide carbanion with the remotely functionalized long chain alkyl iodides have been demonstrated to accomplish the concise and efficient synthesis of Helicobacter pylori antibiotics, the CJ-molecules, and sporotricale methyl ether.

Copper-catalyzed intramolecular N-arylation of quinazolinones: facile convergent approach to (-)-circumdatins H and J - Kshirsagar, Umesh A.; N. P. Argade (Organic Letters, 2010)
A copper-catalyzed intramolecular N-arylation of a quinazolinone nucleus that furnished the central benzodiazepine core unit has been demonstrated to accomplish an efficient convergent total synthesis of (-)-circumdatins H and J.

General approach to 2,4-dialkyl-3-carboxybutyrolactones: an efficient synthesis of (+/-)-striatisporolide A and (+/-)-lichesterinic acid - Patel, Ramesh M.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
Starting from 2-alkylidene-3-methylsuccinimides, simple and efficient synthesis of the natural products striatisporolide A. lichesterinic acid and lichesterylic acid have been demonstrated via an acid catalyzed hydrolysis, esterification, OsO(4)-dihydroxylation and dehydrative cyclization pathway.
Keywords: 2-Alkylidene-3-methylsuccinimides; dehydrative cyclizations; lichesterinic acid; OsO(4)-dihydroxylation; striatisporolide A; synthesis

Total synthesis of proposed auranthine - Kshirsagar, Umesh A.; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2010)
Starting from CBz-protected glutamic anhydride and Boc-protected o-aminobenzyl amine, the first total synthesis of proposed structure of auranthine has been reported. An intramolecular aza-Wittig reaction involving a lactam carbonyl group that delivered the diazepine core unit was the key step in the synthesis.

Chemoenzymatic total synthesis of potent HIV RNase H inhibitor (-)-1,3,4,5-tetragalloylapiitol - Batwal, Ramesh U.; Patel, Ramesh M.; N. P. Argade (Tetrahedron-Asymmetry, 2011)
Starting from racemic dimethyl 2-acetoxy-3-methylenesuccinate, the chemoenzymatic facile total synthesis of (-)-1,3,4,5-tetragalloylapiitol has been demonstrated via an efficient lipase catalyzed resolution followed by a DIBAL reduction-double gallyolation, osmium tetroxide dihydroxylation-double gallyolation, and reductive global O-benzyl deprotection pathway. (C) 2010 Elsevier Ltd. All rights reserved.

Efficient convergent access to spiroketal segment of (+)-spiroxaline methyl ether - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2011)
Starting from trimethylsilylacetylene, a facile synthesis of optically pure spiroketal unit of (+)-spiroxaline methyl ether has been described. The synthesis entails stepwise alkylation and acylation of an alkyne with two different readily available chiral building blocks followed by the reductive in situ regio- and stereoselective spiroketalization pathway.
Keywords: (+)-spiroketal segment synthesis; (R)-gamma-valerolactone; (R)-oxirane; alkyne; nucleophilic reactions

Intramolecular chemoselective acylation of a suitably substituted isoindole: synthesis of (+/-)-chilenine and (+/-)-deoxychilenine - Wakchaure, Prasad B.; N. P. Argade (Synthesis-Stuttgart, 2011)
Starting from 3,4-dimethoxyhomophthalic anhydride and 6-bromohomopiperonylamine, concise and efficient syntheses of Chilean berberis products chilenine and deoxychilenine have been demonstrated via partially divergent routes by taking advantage of facile air-oxidation of homophthalimide along with intramolecular chemoselective acylation as the key steps.
Keywords: chemoselective acylation; chilenine; deoxychilenine; homophthalic anhydride; isoindole; Total synthesis

Regio- and stereoselective selenium dioxide allylic oxidation of (E)-dialkyl alkylidenesuccinates to (Z)-allylic alcohols: synthesis of natural and unnatural butenolides - Patel, Ramesh M.; Puranik, Vedavati G.; N. P. Argade (Organic & Biomolecular Chemistry, 2011)
The first SeO(2) induced (Z)-selective allylic alcohol formation of dialkyl alkylidenesuccinates has been demonstrated to accomplish one-step syntheses of several essential butenolides and fused butenolides via an unusual E- to Z- carbon-carbon double bond isomerisation followed by the lactonization pathway. The observed regio- and stereoselective SeO(2) allylic oxidation protocol has also been extended to the diastereoselective total synthesis of bioactive natural product isomintlactone, its direct conversion to mintlactone and an example of the base-catalyzed intramolecular rearrangement of gamma-lactone to delta-lactone.

Regioselective monoalkylation of dimethyl alkylidenesuccinates: simple approach to dialkyl-substituted maleic anhydrides including chaetomellic acid A - Kshirsagar, Umesh A.; N. P. Argade (Synthesis-Stuttgart, 2011)
Natural and nonnatural dialkylmaleic anhydrides were readily prepared from dimethyl alkylidenesuccinates by sodium hexamethyldisilazide-induced selective monoalkylation followed by base-catalyzed hydrolysis.
Keywords: alkylations; Esters; furans; heterocycles; maleic anhydrides

Regioselective NaBH4 and DIBAL-H reductions of 3,4-dimethoxyhomopiperonylphthalimide: concise and efficient synthesis of nuevamine and isonuevamine - Wakchaure, Prasad B.; Kunte, Sunita S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2011)
Facile synthesis of nuevamine and isonuevamine has been reported via the regioselectivc reduction of hindered and unhindered carbonyl groups of 3,4-dimethoxyhomopiperonylphthalimide, respectively using sodium borohydridc and diisobutylaluminum hydride, Mowed by an acid catalyzed intramolecular dehydrative cyclization pathways. The chemistry involved in obtaining the regioselectivity has been discussed in brief.
Keywords: 6-dimethoxyhomophthalimide; intramolecular dehydrative cyclizations; isonuevamine; N-Homopiperonyl-5; nuevamine; regioselective reductions; synthesis

Facile synthesis of oxyavicine - Jangir, Ravi; N. P. Argade (RSC Advances, 2012)
Starting from dimethyl 3,4-methylenedioxyhomophthalate, a concise total synthesis of oxyavicine has been described via the base catalyzed monoalkylation, homophthalimide formation, oxidative selective iodination, regioselective reductive dehydration and an intramolecular Heck coupling reaction followed by the oxidation pathway with 16% overall yield in six steps.

Palladium-catalyzed routes to geranylated or farnesylated phenolic stilbenes: synthesis of pawhuskin C and schweinfurthin J - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2012)
Starting from double MOM-protected phloroglucinol, the facile total syntheses of bioactive natural products pawhuskin C and schweinfurthin J were accomplished in good overall yields. The Heck, Stille, or Suzuki coupling reactions of two different electron-rich phenolic segments bearing geranylated or farnesylated units were involved in the decisive step. The Sonogashira coupling reaction followed by palladium-catalyzed chemo-and stereoselective cis-reduction of an alkyne unit and subsequent isomerization to give the desired natural products is also described.
Keywords: geranylated or farnesylated stilbenes; Natural products; palladium-catalyzed coupling reactions; phloroglucinol; Total synthesis

Sonogashira coupling reactions of bromomaleimides: route to alkyne/cis-Alkene/Alkyl maleimides: synthesis of luffarin X and cacospongionolide C - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2012)
Palladium-catalyzed Sonogashira coupling reaction of bromomaleimides with a diverse range of terminal alkynes has been demonstrated to furnish the corresponding alkynylmaleimides in very good yields. This coupling reaction followed by selective reduction of the triple bond to single bond have been utilized as the decisive steps to accomplish the first total synthesis of natural products (+/-)-luffarin X and (+/-)-cacospongionolide C.

Synthetic studies towards NG-121: diastereoselective synthesis of NG-121 methyl ether - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2012)
Starting from unsymmetrically O-protected methyl 4-bromo-3,5-dihydroxybenzoate, a facile synthesis of the methyl ether of bioactive natural product NG-121 was accomplished in very good overall yield. The key steps were: Stille coupling reaction of the farnesyl unit with the electron-rich phenolic segment; hydroxy-directed selective epoxidation of the farnesyl chain along with concomitant phenol-driven intramolecular regio- and diastereoselective ring closure to the corresponding hydroxybenzopyran; and regioselective formylation followed by in situ reductive lactonization.
Keywords: 4-bromo-3; 5-dihydroxybenzoate; formylation; intramolecular cyclization; lactonization; NG-121 methyl ether; Stille coupling

Aryne insertion reactions leading to bioactive fused quinazolinones: diastereoselective total synthesis of cruciferane - Vaidya, Sagar D.; N. P. Argade (Organic Letters, 2013)
Insertion reactions of an in situ generated arynes to a variety of suitably substituted 1,3-quinazolin-4-ones have been demonstrated for a new efficient one-step approach to a diverse range of fused quinazolinone architectures. The present protocol has been effectively utilized to accomplish the concise total synthesis of recently isolated bioactive natural products tryptanthrin, phaitanthrins A-C, and cruciferane.

Biology-orientated synthesis of putrescine bisamides gigantamide A, dasyclamide, and cucullamide - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2013)
Starting from putrescine and the requisite carboxylic acids, first syntheses of bioactive natural products gigantamide A, dasyclamide, and cucullamide were accomplished in very good overall yields using an appropriate sequence of dehydrative coupling reactions. The syntheses of the corresponding dehomo analogues of these natural products are also described. Regioselective diisobutylaluminum hydride reduction of an unhindered carbonyl group in citraconimide is the key step.
Keywords: dehydrative coupling reactions; diamines; natural and unnatural bisamides; regioselective reduction; synthesis

Enantioselective total synthesis of desbromoarborescidines A-C and the formal synthesis of (S)-deplancheine - Mondal, Pravat; N. P. Argade (Journal of Organic Chemistry, 2013)
Starting from Boc-protected tryptamine and (S)-tetrahydro-5-oxo-2-furancarboxylic acid, facile enantioselective total synthesis of desbromoarborescidines A-C and the formal synthesis of (S)-deplancheine have been accomplished via a common intermediate (S)-indolo[2,3-a]quinolizine. Synthesis of enantiomerically pure (S)-acetoxyglutarimide, stereoselective reductive intramolecular cyclization, hydroxyl group assisted in situ N-Boc-deprotection, selective deoxygenation, of the xanthate ester, and lactam hydrolysis followed by an appropriate exchange of nitrogen regioselectivity in intramolecular cyclization were the decisive steps.

Palladium-promoted [2+2+2] cocyclization of arynes and unsymmetrical conjugated dienes: synthesis of justicidin B and retrojusticidin B - Patel, Ramesh M.; N. P. Argade (Organic Letters, 2013)
A facile synthesis of natural and unnatural arylnaphthalenes has been demonstrated via the unprecedented palladium-promoted [2 + 2 + 2] cocyclization of arynes and unsymmetrical conjugated dienes using the N-heterocyclic carbene as a ligand. The unsymmetrical dienes used herein are actually alpha-coupled acrylate - cinnamate combinations bearing two beta-positive carbons and follow the key [2 + 2 + 2] cocyclization pathway.

Reactivity umpolung in intramolecular ring closure of 3,4-disubstituted butenolides: diastereoselective total synthesis of paeonilide - Deore, Prashant S.; N. P. Argade (Organic Letters, 2013)
Remarkable reactivity reversal stratagem in 3,4-disubstituted butenolides under acidic conditions is described. Design of a suitably substituted multifunctional butenolide followed by an acid-catalyzed chemo- and diastereoselective intramolecular ring closure via the reactivity umpolung has been demonstrated to accomplish a concise total synthesis of paeonilide. Overall, the present protocol involves one-pot reduction of an a,alpha,beta-unsaturated carbon carbon double bond and intramolecular nucleophilic insertion of oxygen function at the electron-rich gamma-position of butenolide. The involved mechanistic aspects have also been discussed.

Base-stimulated 1,2-, 1,4-, and 1,6-eliminations in suitably substituted alkylidenesuccinates leading to natural and unnatural conjugated alkenyl(methyl)maleic anhydrides - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2014)
With dimethyl maleate as the starting material, facile stereoselective syntheses of natural and unnatural conjugated alkenyl(methyl)maleic anhydrides have been described. The key reactions were base-endorsed novel 1,2-, 1,4-, and 1,6-eliminations in the corresponding alkylidenesuccinate derivatives. The 1,2-eliminations in cyclic carbonate and sulfite by regioselective abstraction of methine protons with the respective release of CO2 and SO2 provided a conjugated ketone product. The characteristic 1,4- and 1,6-elimination reactions with respective release of acetone and mesylate furnished the corresponding unsaturated alcohols. The obtained allylic alcohols were transformed into conjugated alkenyl(methyl)maleic anhydrides via oxidation followed by a Horner-Wadsworth-Emmons reaction pathway in very good yields. The mechanistic aspects involved in these significant elimination reactions have also been described in brief.

Concise account of the chemistry of valuable alkyl(methyl)maleic anhydrides - Deore, Prashant S.; Haval, Kishan P.; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
A large number of significant bioactive natural and synthetic alkyl(methyl)maleic anhydrides are known in the contemporary literature. A broad range of suitably functionalized substrates have been tailored to accomplish concise and efficient syntheses of an array of alkyl(methyl)maleic anhydrides employing a variety of elegant synthetic strategies. This review presents a brief literature account of the isolation and activity of these important target compounds with a special emphasis on their synthesis.
Keywords: alkyl(methyl)maleic anhydrides; bioactivity; dimethylmaleic anhydride; isolation; nucleophilic reactions; Total synthesis

Dimethyl homophthalates to naphthopyrans: the total synthesis of arnottin I and the formal synthesis of (-)-arnottin II - Jangir, Ravi; N. P. Argade (RSC Advances, 2014)
A simple and efficient 3-step synthetic protocol has been reported for dimethyl homophthalates to naphthopyrans. Starting from dimethyl 2,3-dimethoxyhomophthalate, a practical synthesis of arnottin I has been described via a base catalyzed mono-alkylation, the selective hydrolysis of an aliphatic ester moiety, two consecutive intramolecular cyclizations and an oxidative aromatization pathway with a very good overall yield. The involved intramolecular acylation followed by an associated enolative lactonization was the decisive step. The synthesis of dihydroarnottin I also completes the formal synthesis of (-)-arnottin II.

Diversity oriented convergent access for collective total synthesis of bioactive multifunctional carbazole alkaloids: synthesis of carbazomycin A, carbazomycin B, hyellazole, chlorohyellazole, and clausenaline D - Markad, Shivaji B.; N. P. Argade (Organic Letters, 2014)
Facile syntheses of imperative carbazole alkaloids carbazomycin A, carbazomycin B, hyellazole, chlorohyellazole, and clausenaline D have been demonstrated starting from readily available Boc-protected 3-formylindole and dimethyl maleate. The suitably substituted aromatic rings have been designed comprising three/four significant C-C bond forming reactions. The competent Wittig reaction, selective monoalkylations, one-pot regioselective Weinreb amide formation and Boc-deprotection, well designed Grignard reactions, dehydrative intramolecular cyclizations, and Baeyer-Villiger rearrangement of aromatic aldehydes were the main features.

Facile synthesis of the isoquinoline alkaloids doryanine and oxyhydrastinine - Jangir, Ravi; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
Starting from 4,5-(methylenedioxy)homophthalic acid, a concise and efficient synthesis of the isoquinoline alkaloids dory-anine and oxyhydrastinine is described via the corresponding homophthalimide utilizing a one-pot regioselective reductive dehydration and catalytic hydrogenation pathway.
Keywords: dehydration; homophthalic acid; homophthalimide; isoquinoline alkaloids; regioselective reduction

Metal-catalyzed cross-coupling reactions of halomaleic anhydrides and halomaleimides: synthesis of structurally interesting and biologically important natural and unnatural products - Deore, Prashant S.; N. P. Argade (Synthesis-Stuttgart, 2014)
This brief review presents a concise literature account of the metal-catalyzed cross-coupling reactions of halomaleic anhydrides and halomaleimides leading to significant synthetic and natural products. Metal-catalyzed Heck, Suzuki-Miyaura, Stille-Migita, Negishi, Hiyama, and Sonogashira cross-coupling reactions with palladium as the key element are discussed. The metal-catalyzed exchange of a vinylic leaving group by a carbon nucleophile, the SNV reaction, gives a diverse range of bioactive natural and unnatural products.
Keywords: bioactive natural and unnatural products; halomaleic anhydride; halomaleimide; metal-catalyzed cross-coupling; synthesis

Synthesis of chenopanone - Deore, Prashant S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Starting from glyoxalic acid, a facile three step approach to chenopanone has been described utilizing the Barbier reaction as a key step.
Keywords: acid hydrolysis; Barbier reaction; chenopanone; condensation; Glyoxalic acid; isovaleraldehyde; synthesis

Synthesis of (+)-harmicine - Mondal, Pravat; N. P. Argade (Synthesis-Stuttgart, 2014)
A facile convergent access to the important indole alkaloid (+)-harmicine is described, starting from tryptamine and (R)-acetoxysuccinic anhydride via the corresponding acetoxysuccinimide in very good overall yield. Regioselective reduction of an unsymmetrical imide carbonyl group and acid-catalyzed stereoselective intramolecular cyclization were the key features involved. The directing group to induce asymmetry was finally detached via the corresponding iodide by using tributyltin hydride chemistry.
Keywords: alkaloids; cyclization; imides; reduction; stereoselective synthesis

Biomimetic synthesis of phaitanthrin e involving a fragmentation of sp(3) carbon-carbon bond: synthesis and rearrangement of phaitanthrin D to phaitanthrin E - Vaidya, Sagar D.; N. P. Argade (Organic Letters, 2015)
A biogenetic type total synthesis of alkaloids phaitanthrin D and phaitanthrin E has been described. The Csp(3)-Csp(3) bond cleavage with the release of several heteroatoms bearing unexpected leaving groups in intramolecular substitution reactions on an iminium double bond in the quinazolinones has been demonstrated using HMDS/ZnCl2 or NaHMDS. The mechanistic aspects have been supported by isolation and characterization of appropriate intermediates.

Chemoenzymatic collective synthesis of optically active hydroxyl(methyl)tetrahydronaphthalene-based bioactive terpenoids - Batwal, Ramesh U.; N. P. Argade (Organic & Biomolecular Chemistry, 2015)
Starting from succinic anhydride and 2-methylanisole, a chemoenzymatic collective formal/total synthesis of several optically active tetrahydronaphthalene based bioactive natural products has been presented via advanced level common precursors; the natural product and antipode (-)/(+)-aristelegone B. Regioselective benzylic oxidations, stereoselective introduction of hydroxyl groups at the alpha-position of ketone moiety in syn-orientation, efficient enzymatic resolutions with high enantiomeric purity, stereoselective reductions, samarium iodide induced deoxygenations and tandem acylation-Wittig reactions without racemization and/or eliminative aromatization were the key features. An attempted diastereo-selective synthesis of (+/-)-vallapin has also been described.

Sulfuryl chloride promoted gem-dichlorination-dehydrochlorination in alkyl benzothiazinylacetates: synthesis of the skeleton of trichochrome pigments - Jangir, Ravi; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2015)
Chemo- and stereoselective total synthesis of the basic trichochrome skeleton is described starting from o-aminothiophenol and maleic anhydride in very good overall yield. The process involves the synthesis of the corresponding 1,4-benzothiazin-2-ylacetates followed by their sulfuryl chloride induced dihalogenation-dehydrohalogenation and a second condensation with o-aminothiophenol as key steps.
Keywords: condensations; halogenation; maleic anhydride; o-aminothiophenol; trichochrome framework

Synthesis of yangjinhualine A - Deore, Prashant S.; Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2015)
Selective reduction of 3-(4-hydroxyphenyl)-2-methylmaleic anhydride provides access the corresponding gamma-hydroxybutenolide natural product yangjinhualine A.
Keywords: anhydrides; lactones; Natural products; reduction; Regioselectivity

Biomimetic collective total synthesis of bioactive carbazole alkaloids indizoline, mafaicheenamine A, claulamine A, claulansine A, and the proposed claulamine E - Markad, Shivaji B.; N. P. Argade (Journal of Organic Chemistry, 2016)
The common precursor 1-methoxy-2-prenyl-3-carbomethoxycarbazole was synthesized from dimethyl indolylmethylenesuccinate in four steps. Well-planned reductive and/or oxidative transformations and intramolecular cyclizations were performed on a pivotal common precursor to accomplish collective first total synthesis of titled natural products and proposed Claulamine E. Burgess reagent induced formation of kinetically controlled product Claulamine A, and intramolecular cyclizations to form bicyclic claulansine A were the key reactions. An alternatively attempted synthesis failed to provide the structural isomer of proposed Claulamine E.

Chemoenzymatic access to (+)-artabotriol and its application in collective synthesis of (+)-grandiamide D, (-)-tulipalin B, (+)-spirathundiol, and (+)-artabotriolcaffeate - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2016)
Starting from dimethyl (+/-)-2-hydroxy-3-methylenesuccinnate chemoenzymatic collective formal/total synthesis of enantiomerically pure bioactive natural products has been described via the advanced level common precursor (+)-artabotriol. An efficient enzymatic resolution with high enantiomeric purity, selective diester to diol reduction, and requisite dehydrative coupling reactions without any racemization are the significant topographies.
Keywords: (+)-artabotriol; collective synthesis; coupling reactions; dimethyl (+/-)-2-hydroxy-3-methylenesuccinate; Enzymatic resolution; Natural products; reduction

Stereoselective synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine: observation of a substrate dependent diastereoselectivity reversal of an aldol reaction - Mondal, Pravat; N. P. Argade (Organic & Biomolecular Chemistry, 2016)
Starting from (-)-acetoxyglutarimide, the enantioselective multistep synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine has been demonstrated via a common hydroxyl-lactam intermediate with very good overall yields. The acetoxy function from (-)-acetoxyglutarimide was initially used as a handle to induce enantioselectivity and then as a latent source of the ketone carbonyl group. Most importantly, substrate dependent reversal of the diastereoselectivity in ester aldol reactions of hexahydroindolo[2,3-a] quinolizinones has been reported.

Synthesis of (-)-phaitanthrin D and (+)-dihydropyrroloindoloquinazolinone - Vaidya, Sagar D.; N. P. Argade (Synthesis-Stuttgart, 2016)
The synthesis of (-)-phaitanthrin D and (+)-dihydropyrroloindoloquinazolinone are reported starting from the corresponding especially designed enantiomerically pure pivotal anthranilamide based building blocks using HMDS/ZnCl2 and NaHMDS.

Formal synthesis of bioactive indole alkaloids eburnamonine, eburnaminol, and vindeburnol - Mondal, Pravat; Argade, Narshinha P. (Synthesis-Stuttgart, 2017)
Starting from (+/-)-3-acetoxyglutarimide, diastereoselective formal synthesis of indole alkaloids (+/-)-eburnamonine, (+/-)-eburnaminol, and (+/-)-vindeburnol have been demonstrated via a common intermediate (+/-)-1-hydroxy-12-tosyl-2,3,6,7,12,12b-hexahydroindolo[2,3a] quinolizin-4(1H)-one in very good overall yields. The acetoxy group from (+/-)-3-acetoxyglutarimide was first used to induce the diastereoselectivity and also as a latent source of ketone carbonyl group. The stereoselective eliminations, reductions, and intramolecular cyclizations were the involved key steps.
Keywords: cyclizations; eburnaminol; eburnamonine; elimination; hexahydroindoloquinolizinone; reduction; vindeburnol

Rearrangement of imine double bond in activated quinazolinones: synthesis of phaitanthrin E - Vaidya, Sagar D.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2017)
Wolff-Kishner reduction of tryptanthrin to indoloquinazolinone followed by lithium diisorpropylamide induced acylation of the active methylene group with methyl chloroformate directly furnishes the phaitanthrin E in very good yield. Similar acylations of indoloquinazolinone have also been performed with four different acyl chlorides. In all examples, facile rearrangement of imine double bond from quinazolinone to indole moiety to form the corresponding alpha,beta-unsaturated carbonyl system is observed.

Total synthesis of bioactive canthine alkaloid cordatanine comprising in situ double oxidative aromatization of tetrahydrocarbazole - Shelar, S. V.; N. P. Argade (ACS Omega, 2017)
Starting from tryptamine and methoxymaleic anhydride, concise and efficient total synthesis of cordatanine has been accomplished via regioselective reduction of methoxymaleimide, acid-catalyzed intramolecular cyclization of the formed lactamol, in situ stepwise oxidations leading to aromatization, and intramolecular cyclization with the exchange of N-regioselectivity. An attempted synthesis of regioisomeric natural product zanthochilone has been described in brief with reversal of reduction selectivity.

Total synthesis of (+/-)/(+)-subincanadine E and determination of absolute configuration - Kalshetti, Manojkumar G.; N. P. Argade (Journal of Organic Chemistry, 2017)
A facile synthesis of (+/-)-subincanadine E was described from tryptamine-based maleimide. 1,2-Addition of Grignard reagent to maleimide, internal activation of formed lactamol for in situ 1,4-addition of Grignard reagent, and associated position-specific allylic rearrangement in diastereoselective Pictet-Spengler cyclization were the key steps. Enantioselective first total synthesis of naturally occurring cytotoxic (+)-subincanadine E was also accomplished from (S)-acetoxysuccinimide via an unusual syn-addition of cuprate to the alpha/beta-unsaturated lactam. Sinister absolute configuration was assigned to (+)-subincanadine E on the basis of total synthesis. (S)-Acetoxy group in the succinimide precursor was initially employed to impart regio- and stereoselectivity and then as a suitable leaving group to generate the desired conjugated lactam.

Total synthesis of tetrahydroisoquinoline-based bioactive natural products laudanosine, romneine, glaucine, dicentrine, and their unnatural analogues isolaudanosine and isoromneine - Jangir, Ravi; Argade, Narshinha P. (Synthesis-Stuttgart, 2017)
Starting from suitably substituted homophthalic acids, total synthesis of titled alkaloids have been demonstrated in very good yields. The obtained natural products laudanosine and romneine were utilized to accomplish synthesis of two isoquinoline-based alkaloids glaucine and dicentrine. Base-induced selective generation of two different types of benzylic carbanions, their coupling reactions with 3,4-dimethoxybenzyl mesylate, and the regioselective iodination followed by intramolecular aryl-aryl coupling reactions to form the fused biaryl systems were the strategic steps.

Diastereoselective synthesis of (A±)- epi-subincanadine C - Kalshetti, Manojkumar; N. P. Argade (ACS Omega, 2018)
Starting from indolylmaleimide, concise and efficient total synthesis of (±)-epi-subincanadine C was described via stereoselective Wittig olefination, base-induced selective mono-prenylation, regioselective Grignard reaction, diastereoselective Pictet–Spengler cyclization, regioselective oxidative carbon–carbon double-bond cleavage, one-pot reductions, and intramolecular cyclization pathway. An attempted synthesis of (±)-subincanadine C via diastereoselective Grignard addition to the α,β-unsaturated γ-lactam or diastereoselective reduction of a carbon–carbon double bond also resulted in yet another route to (±)-epi-subincanadine C.

First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin

Regioselective and stereoselective reductive aziridinium ring cleavage leading to azabicyclodecane architecture: enantioselective synthesis of (+)-subincanadine F - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Journal of Organic Chemistry, 2018)
Enantioselective synthesis of cytotoxic indole alkaloid (+)-subincanadine F was accomplished starting from the corresponding (S)-acetoxysuccinimide via aziridinium ring formation and its reductive ring expansion route. Regioselective and stereoselective reductive aziridinium carbon-nitrogen bond cleavage comprising ring expansions was a key step. The (S)-OMOM protection of the hydroxyl moiety adjacent to a benzylic carbon of an in situ formed aziridinium system was necessary for lithium borohydride-induced reductive ring expansions, and it also served as a latent source of an essential ketone carbonyl group for the generation of an alpha,beta-conjugated system.

Solid state auto-inversion of C-centrochirality: enantioselective total synthesis of furocarbazolones (-)-epi-claulansine D and (-)-claulansine D and pyranocarbazolone (+)-epi-claulansine C - Markad, Shivaji B.; N. P. Argade (Journal of Organic Chemistry, 2018)
Starting from dimethyl (E)-2-{[(1-tert-butoxycarbonyl)-1H-indol-3-yl]methylene}succinate and (R)-2,2,5,5-tetramethyl-1,3-dioxolane-4-carbaldehyde, facile synthesis of (-)-epi-claulansine D was accomplished via condensation and two intramolecular cyclizations. The (-)-epi-claulansine D in the solid state exists in a metastable form, and after an induction period of 30-90 days, it underwent complete epimerization to exclusively deliver the desired natural product (-)-claulansine D in quantitative yield. The witnessed inversion of C-centrochirality in the solid state is conceptually novel and takes place for relatively higher crystal stability reasons. Base-catalyzed ring expansion of both (+/-)/(-)-epi-claulansine D and (+/-)/(-)-claulansine D resulted in (+/-)/(+)-epi-claulansine C in very good yields.

Progress in total synthesis of subincanadine alkaloids and their congeners - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2019)
A concise account of isolation, characterization, bioactivity, plausible biogenetic pathways, and most importantly, total synthesis of structurally fascinating and biologically imperious indole-based subincanadine alkaloids and their biogenetic congeners are described in the present review with special emphasis on total synthesis and therein an involved set of key reactions.

Regioselective oxidation of indoles to 2-oxindoles - Shelar, Santosh V.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2019)
Facile regioselective oxidation of indoles to 2-oxindoles promoted by sulfuric acid adsorbed on silica gel is reported. The demonstrated practical site-selective heterogeneous oxidation reactions conveniently take place with a broad substrate scope and functional group tolerances. The present oxidation strategy is also employed to accomplish the total synthesis of natural products donaxaridine and donaxarine. On the basis of analytical and spectral data it is evidenced that donaxarine stays in equilibrium with its hydrated ring opened form. The structural features essential for this type of oxidation and plausible mechanism are discussed in brief.

Stereoselective synthesis of subincanadine alkaloids framework - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
Starting from, N-tosyltryptamine and (S)-acetoxysuccinic anhydride, a facile synthesis of (-)-indolizinoindolone has been demonstrated as a basic structural outline of bioactive subincanadine alkaloids. Regioselective Grignard reaction with (S)-acetoxysuccinimide, stereoselective intramolecular cyclization to form (-)-indolizinoindolone skeleton and TiCl4 induced condensation with acetaldehyde for stereoselective generation of exocyclic carbon carbon double bond are the key features.
Keywords: (S)-Acetoxysuccinimide; alane reduction; condensation; Grignard reaction; indolizinoindolone; PCC-oxidation; stereoselective Pictet-Spengler cyclization

Chemoselective ring closure of 4-(3-Methyl-2-oxo-2,5-dihydro-1H-pyrrol-1-yl)butanal leading to pandalizine A - Yadav, Mahesh B.; Pandhade, Kailas R.; Argade, Narshinha P. (ACS Omega, 2020)
Starting from methylmaleic anhydride, a facile total synthesis of pandalizine A alkaloid is described via the regioselective reduction of methylmaleimide and acid-catalyzed enolization of 4-(3-methyl-2-oxo-2,5-dihydro-1H-pyrrol-1-yl)butanal followed by chemoselective intramolecular dehydrative cyclization as the key steps. It is noteworthy that the analogous model system with an additional beta-methyl group followed an alternative chemoselective intermolecular aldol condensation pathway.

Facile synthesis of indolizinoindolone, indolylepoxypyrrolooxazole, indolylpyrrolooxazolone and isoindolopyrazinoindolone heterocycles from indole and imide derivatives - Shelar, Santosh V.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2021)
Chemo-, regio- and diastereoselective coupling reactions of indole with imide derivatives leading to unique heterocyclic systems are demonstrated. Acid-induced 3-position coupling reactions of indole with cyclic imide derived lactamols followed by acid promoted 2-position cyclizations with the corresponding aldehydes are described to obtain the indolizinoindolones and benzoindolizinoindolones. Base induced 2-position coupling reactions of N-tosylindole with N-(2-iodoethyl)imides and the subsequent cyclizations provide indolylepoxypyrrolooxazole, indolylpyrrolooxazolone and indolyloxazoloisoindolone. Reductive cleavage of indolyloxazoloisoindolone to the corresponding alcohol followed by mesylation and base promoted N-cyclization affords the in situ air-oxidized pentacyclic product hydroxyisoindolopyrazinoindolone. A regioisomeric structural revision of the natural product from 1,2,5,6,7,11c-hexahydro-3H-indolizino[7,8-b]indol-3-one to 1,2,5,6,11,11b-hexahydro-3H-indolizino(8,7-b)indol-3-one is also reported in the present studies focussed on the methodologies for heterocyclic synthesis.

Wittig reactions of maleimide-derived stabilized ylides with alkyl pyruvates: concise approach to methyl ester of (+/-)-chaetogline A - Shelar, Santosh V.; Argade, Narshinha P. (Synthesis-Stuttgart, 2021)
A facile synthesis of methyl ester of chaetogline A is reported starting from the corresponding methyl 1-methyltryptophanate-derived- maleimide. A stereoselective Wittig olefination with a carbonyl function in methyl pyruvate followed by phosphorous pentoxide-induced- regioselective dehydrative cyclization are the essential reactions. An acid-induced thermodynamically driven stereoselective beta- to alpha-position migration of the exocyclic C=C bond unit in ethyl tetrahydroindolizinoindolylidenepropanoate is described.
Keywords: Amino acid; chaetogline A; dehydrative cyclization; maleimide; methyl pyruvate; Natural product; Wittig reaction

Wittig reactions of maleimide-derived stabilized ylides with alkyl pyruvates: concise approach to methyl ester of (±)-chaetogline A - Argade, Narshinha P.; Shelar, Santosh V. (Synthesis, 2021)
A facile synthesis of methyl ester of chaetogline A is reported starting from the corresponding methyl 1-methyltryptophanate-derived maleimide. A stereoselective Wittig olefination with a carbonyl function in methyl pyruvate followed by phosphorous pentoxide-induced regioselective dehydrative cyclization are the essential reactions. An acid-induced thermodynamically driven stereoselective β- to α-position migration of the exocyclic C=C bond unit in ethyl…

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction